KAJIAN PERKEMBANGAN PERDAGANGAN INTERNASIONAL KARET INDONESIA KE NEGARA ANGGOTA ISO/TC 45 - Retno Suciati (Badan Standardisasi Nasional, 2006)
As member in organization of international standard ISO, it expected that Indonesia could conduit its importance to survive in the globalization era, that using standards and conformity assessment as a reference in commerce transaction. As one of biggest rubber producer in the world and have importance in international trade, it needs any study of the growth of international trade of Indonesian rubber to all countries destination that concern to international standard related rubber. This study is focused to the countries destination that as a member of international organization for standardization (ISO) especially member of ISO/TC 45, where is Indonesia as a member. The results of this study show that Indonesian rubber export to the ISO/TC 45 member countries destination is growth higher rather than to other countries destination. Its show that the export to the ISO/TC 45 member countries destination is dominated by SITC 231 and to the other countries destination is dominated by SITC 231 and 625.